Vaje za stabilen trup so pomemben del sodobne telovadbe - Urbančič, Rok (Šport (Ljubljana), 2017)
In recent years, the so-called functional training has been steadily gaining popularity. One of the key aspects of this type of training is developing and maintaining certain movement patterns which are important in everyday lives. However, performing such complex movement exercise routines requires great stability and mobility of the torso, known also as core stability and mobility. Having taken this into account, we have combined and demonstrated with pictures some core stability exercise routines in which exercises follow one another in logical succession from easier to more difficult, and from simpler to more complex exercises. Better core stability successfully prevents injuries and guarantees a more efficient performance of different movement patterns in everyday chores, as well as in various sports.
Keywords: core stability exercises; functional training; funkcionalna vadba; sport; šport; telovadba; vaje za stabilen trup